2022
DOI: 10.1136/bmjophth-2021-000838
|View full text |Cite
|
Sign up to set email alerts
|

Progression to severe visual impairment and blindness in POAG patients: pace and risk factors—a cohort study using German health claims data

Abstract: ObjectiveGlaucoma is a leading cause of severe visual impairment and blindness (SVI/B) worldwide. Hence, it is of utmost importance to explore relevant risk factors and study the pace of progression to SVI/B.Methods and analysisWe used a random sample of 250 000 persons from administrative individual-level health records of the Allgemeine Ortskrankenkassen between 2004 and 2015. We identified 3535 primary open-angle glaucoma (POAG) patients aged 55 and older and followed them for up to 10 years. Monocular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…A study of open-angle glaucoma patients in Italy discovered that characteristics such as family history, myopia, diabetes, and systemic hypertension were linked to bilateral VF damage [18]. According to a Swedish study, the presence of particular additional eye disorders such as secondary glaucoma, retinal vascular occlusion, or age-related macular degeneration enhanced the likelihood of severe vision loss and blindness in POAG patients [19].…”
Section: Resultsmentioning
confidence: 99%
“…A study of open-angle glaucoma patients in Italy discovered that characteristics such as family history, myopia, diabetes, and systemic hypertension were linked to bilateral VF damage [18]. According to a Swedish study, the presence of particular additional eye disorders such as secondary glaucoma, retinal vascular occlusion, or age-related macular degeneration enhanced the likelihood of severe vision loss and blindness in POAG patients [19].…”
Section: Resultsmentioning
confidence: 99%
“…2 POAG is the most common subtype of glaucoma, accounting for approximately three-fives (58.9% of 58.9 million) of all glaucoma cases in 2020, and is the main cause of blindness in glaucoma patients. 3 Moreover, POAG can be categorized into high-tension glaucoma (HTG) and normal-tension glaucoma (NTG) according to the height of the ocular partial pressure at the time of onset. 4 Many epidemiological studies have suggested that many factors, including intraocular pressure (IOP), myopia, race, age, genetic mutation, immune disorders, smoking or drinking, and diabetes mellitus are the main risk factors for POAG.…”
Section: Introductionmentioning
confidence: 99%